Nazi Characters in German Propaganda and Literature - Lorenz, Dagmar C. G. (2018)
Antifascist literature repurposed Nazi stereotypes to express opposition. These stereotypes became adaptable ideological signifiers during the political struggles in interwar Germany and Austria, and they remain integral elements in today’s cultural imagination.; Readership: Scholars and students of twentieth century German and Austrian culture and Nazi propaganda and ideology; antifascist literature , the production and reproduction of Nazi stereotypes, and gendered Nazi characters.